Storage Quality of Rista with Rosemary Extract as an Antioxidant - Hussain, S. A.; Salahuddin, Mir; Jalal, Heena; Wani, S. A.; Pal , M. A.; Bumla, Nazir (Journal of Meat Science, 2016)
The effect of incorporation of rosemary extract at 0.005% on the quality and storage stability of Rista was studied. All the physico-chemical parameters of raw emulsion, cooked product and gravy showed non-significant difference (p>0.05) between the treatments. Sensory scores of Rista showed non-significant (p>0.05) difference. Further, the cooked product was aerobically packaged in LDPE bags and stored at 4+1oC for a period of 3 weeks during which the product samples were drawn at weekly intervals and evaluated for pH, 2-thiobarbituric acid (TBA) value, microbiological quality and sensory attributes. The results indicated that the pH and TBA value of Rista samples increased significantly (p<0.05) with the advancement of storage. However, the values even at the end of storage period were well below the reported safe limits and not indicative of any rancidity. The total plate count and coliform count of Rista samples increased significantly (p<0.05) during storage. The yeasts and moulds were detected only from day 14 of storage and then increased significantly (p<0.05) by the end of day 21 of storage. The microbial counts in general remained low and well within permissible limits even at the end of the storage period. The results of sensory evaluation revealed a gradual decrease in the scores of various attributes with the advancement of storage. However, the scores even at the end of storage period remained generally in the range of above six indicating good acceptability of the product.